INOVASI STRATEGI PEMBELAJARAN BERBASIS PROYEK, LATIHAN DAN PRAKTEK (PROJECT, DRILL AND PRACTICE BASED LEARNING) PADA MATA PELAJARAN PAI BERBASIS KURIKULUM MERDEKA. - Ai Siti Hodijah; Alfauzan Amin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Islamic Religious Education (PAI) includes an understanding of religious teachings and how to apply them in everyday life. Learners are faced with various complex and diverse challenges in the current era of technology and globalization. The purpose of this research is to find out the basic concepts and the importance of applying project-based learning strategies, drill and practice in increasing the creativity of students in PAI subjects based on the independent curriculum. The research method used in this research is the literature method which uses books, journals and articles as sources of information. The results of this study are thatthe project-based learning strategy (PjBL), drill and practice can increase understanding, creativity, and help students to innovate according to their knowledge and help students build cooperation between school residents, with exercises and practices carried out continuously can also be used as a reference for evaluating the learning process for an educator.